2019
DOI: 10.1021/acs.est.9b05241
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Particulate Matter, Ozone, and Nitrogen Oxides during Urban Smoke Events in the Western US

Abstract: Urban ozone (O 3 ) pollution is influenced by the transport of wildfire smoke but observed impacts are highly variable. We investigate O 3 impacts from smoke in 18 western US cities during July−September, 2013− 2017, with ground-based monitoring data from air quality system sites, using satellite-based hazard mapping system (HMS) fire and smoke product to identify overhead smoke. We present four key findings. First, O 3 and PM 2.5 (particulate matter <2.5 μm in diameter) are elevated at nearly all sites on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 89 publications
6
74
0
2
Order By: Relevance
“…Before Lockdown (BL), During Lockdown (DL), and Resumption denote the periods of January 1-January 23, January 24-February 15, and February 16-February 28, respectively. The diurnal variations of mean O 3 concentrations for the periods of BL and DL in (a, b) clearly indicate that the mean O 3 concentrations for the non-photochemical reaction times from 20:00 PM to 9:00 AM (local time) during lockdown in 2020 were 53.7 and 58.0 μg m −3 in the urban and rural areas, respectively, much higher than the corresponding values (i.e., 18.8 and 35.6 μg m −3 in the urban and rural areas, respectively) before lockdown ◂ sink of HO 2 and NO x radicals, and chemical titration of NO (Buysse et al 2019;Li et al 2019;Yu et al, 2014).…”
Section: Inter-species Correlations In the Observationsmentioning
confidence: 76%
“…Before Lockdown (BL), During Lockdown (DL), and Resumption denote the periods of January 1-January 23, January 24-February 15, and February 16-February 28, respectively. The diurnal variations of mean O 3 concentrations for the periods of BL and DL in (a, b) clearly indicate that the mean O 3 concentrations for the non-photochemical reaction times from 20:00 PM to 9:00 AM (local time) during lockdown in 2020 were 53.7 and 58.0 μg m −3 in the urban and rural areas, respectively, much higher than the corresponding values (i.e., 18.8 and 35.6 μg m −3 in the urban and rural areas, respectively) before lockdown ◂ sink of HO 2 and NO x radicals, and chemical titration of NO (Buysse et al 2019;Li et al 2019;Yu et al, 2014).…”
Section: Inter-species Correlations In the Observationsmentioning
confidence: 76%
“…The ODR fits in Figures 8a–8f vary widely, but Figure S3 shows that the ΔO 3 /Δ β ratios in the buffer layer and free troposphere decreased exponentially with increasing peak backscatter. A recent analysis of surface measurements by Buysse et al (2019) also found less O 3 production in some denser smoke plumes. Possible reasons for the decrease in Figure S3 include reduced actinic fluxes in the denser smoke plumes, O 3 losses on aerosol surfaces, or changes in the fuels and/or combustion regime.…”
Section: Ozone Production In the Smoke Plumementioning
confidence: 84%
“…), as a part of the NOAA FIREX AQ-2019 field experiment. We chose these sites because they are frequently affected by biomass burning each year [7]. The ambient samples were collected using dual-bed TD tubes at Spokane and Boise from 06/14/2019 08:00 PM to 07/19/2019 09:30 AM and 07/27/2019 11:00 AM to 09/12/2019 03:00 PM, respectively.…”
Section: Application Of the Dual-bed Td Tubes With Voc Auto-samplers mentioning
confidence: 99%
“…Production of O 3 from forest fires is highly variable [6], and each fire is unique in terms of emissions, transport pathway, plume injection heights, and photochemistry. Eulerian grid models often have difficulty accurately modeling downwind O 3 concentrations [4,[7][8][9]. Because of these complexities and the impacts at relatively low particulate matter concentrations, it is critical to develop additional tracers for forest fire influence.…”
Section: Introductionmentioning
confidence: 99%